Report of the Task Force on Projections of Minimum Needs and Effective Consumption Demand - Planning Commission (Planning Commission, 1979)
The Task Force Report on Projections of Minimum Needs and Effective Consumption Demand provides a comprehensive analytical framework for estimating consumption requirements in India, with particular emphasis on poverty alleviation and income-based demand behavior. Prepared for the 1978–83 Five-Year Plan, the report differentiates between normative minimum needs and effective consumption demand, employing the Linear Expenditure System and Engel curves based on National Sample Survey data. Detailed projections are developed across rural and urban populations, commodity groups, and income strata, including alternative poverty-line scenarios. The report establishes caloric norms, corresponding monetary poverty thresholds, and demand elasticities, offering critical insights into consumption dynamics. Its findings serve as a foundational input for policy formulation aimed at meeting minimum living standards while accommodating realistic consumption behavior in a changing economic environment.
Perspective Planning Division Government of India Planning Commission New Delhi January 1979
Perspective Planning Division Government of India Planning Commission New Delhi January 1979
Keywords: Minimum Needs Approach; Effective Consumption Demand; Planning Commission of India; Linear Expenditure System; Engel Curves; Poverty Line Estimation; National Sample Survey; Demand Function Parameters; Consumption Projections; Income Distribution; Rural and Urban Consumption; Five-Year Plan Analysis